Use of The Teaching Manual And Active Learning (Mpdpa) in Improving Communication Skills Among Students - Talib Hashim (Journal of Research in Social Science and Humanities, 2023)
This study reviewed the used of the Active Teaching and Learning Activity Manual (MaPdPA) in improving communication skills in the sixth form curriculum. This study used a combination of design and development research. A quasi-experimental design was also used to see or evaluate the effect of the Active Teaching and Learning Activity Manual (MaPdPA) in improving communication skills. The total amount for the study sample for KR and KK for both groups of students was a total of 120 students consisting of 38 male students and 82 female students. This research instrument consisted of a set of pre- and post-test questions using a 5-point Likert scale to assess the level of mastery of students' soft skills as assessed by the teacher. Quantitative data for this study was analyzed using descriptive and inferential statistics which aimed to describe the statistical data using the MANCOVA test. The results of the MANCOVA test analysis found that there was a significant main effect of the type of treatment using MaPdPA on the students' mastery of communication skills. Through the post-test analysis for the level of mastery of the elements of communication skills, it showed that there was a significant difference in the test mean for both groups of PA and PSA students. The PA student group turned out to have a better level of mastery of communication skills in the post-test mean value compared to the PSA student group. The used of MaPdPA is not only an innovation of BBM for teachers' use but also capable of narrowing the gap in the learning effect to increase the mastery of students' soft skills. As a result, active learning provides benefits in improving the skills of teachers and students in addition to boosting the performance of individual and institutional achievements.